If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2x^2-5x+3x=4
We move all terms to the left:
-2x^2-5x+3x-(4)=0
We add all the numbers together, and all the variables
-2x^2-2x-4=0
a = -2; b = -2; c = -4;
Δ = b2-4ac
Δ = -22-4·(-2)·(-4)
Δ = -28
Delta is less than zero, so there is no solution for the equation
| 3(2x+3)=2(4x-6) | | 2(x-5)=9-3x+6+3x+7 | | 25=286.93(0.9738^x) | | 17t+16=-17+20 | | -20=-4(x+3) | | 6x=4=30 | | 4-x=120+3-10x | | -240x=12x | | 2(5y-4)+y=25 | | -20-11c-5=20-8c | | 2(3x+8)=7x+4 | | (x-12)+(x+54)=180 | | -11+3x=-14 | | 6u+9=-9u+48 | | -5h-8=10+6h+4 | | -3x+17=-5x+20 | | 20=x/2-17 | | -6+8r=9r | | 19=12+17r | | 3/6x+6=1/2x+1/4x | | -9c+8=-2-8c | | 3h+9.7=5.1h-5.63 | | Y=6x*1/(3x^2) | | 3x^2+6x^2=135 | | -18-5x=22 | | 3(2X=3x)=60 | | (3x-x)-(6x+1)=-3x-2 | | 4x+7x+7x+6x=360 | | 2-6d=6-2d | | -8-3v=8-8v-6 | | 4x^2+6x^2=50 | | F(x)=-x+4x-4 |